Uses of Preposition Combinations: An Error Analysis - Sravanan, J.; Lakshmikanthan, B. (Journal of NELTA, 2020)
This study is an attempt to identify the difficulties in the use of the preposition combinations and analyze the causes of errors made by the Engineering students while writing. The subjects of the study comprised of 60 randomly selected first-year students from two engineering colleges located in Tirunelveli city, and they were asked to write an essay. To analyze the collected data, descriptive methods were used. The results show that the Engineering students made errors in the use of prepositions after nouns, verbs, and adjectives due to the mother tongue interference and ignorance of rules. The researchers recommended that the teachers should make an attempt to provide more exposure to the learners to use these combinations and actively engage them through various consciousness-raising activities. Teachers should highlight the collocation rules while teaching; the students will get exposure to collocation in their writing and speaking.